2016
DOI: 10.1089/omi.2016.0105
|View full text |Cite
|
Sign up to set email alerts
|

An Expert Review of Pharmacogenomics of Sickle Cell Disease Therapeutics: Not Yet Ready for Global Precision Medicine

Abstract: Sickle cell disease (SCD) is a blood disease caused by a single nucleotide substitution (T > A) in the beta globin gene on chromosome 11. The single point mutation (Glu6Val) promotes polymerization of hemoglobin S (HbS) and causes sickling of erythrocytes. Vaso-occlusive painful crises are associated with recurrent and long-term use of analgesics/opioids and hydroxyurea (HU) by people living with SCD. The present analysis offers a stateof-the-art expert review of the effectiveness of pharmacogenomics/genetics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 121 publications
0
12
0
Order By: Relevance
“…We initially performed a thorough review of the literature on pharmacogenomics of SCD therapeutics, and identified a list of variants that are potentially associated with pain in SCD (Mnika et al , ). Once the SNPs of interests were identified, we investigated their allele frequencies in African populations present in the 1000 Genomes project (http://www.internationalgenome.org/home), and further narrowed the selection to SNPs that showed high frequency among African populations.…”
Section: Methodsmentioning
confidence: 99%
“…We initially performed a thorough review of the literature on pharmacogenomics of SCD therapeutics, and identified a list of variants that are potentially associated with pain in SCD (Mnika et al , ). Once the SNPs of interests were identified, we investigated their allele frequencies in African populations present in the 1000 Genomes project (http://www.internationalgenome.org/home), and further narrowed the selection to SNPs that showed high frequency among African populations.…”
Section: Methodsmentioning
confidence: 99%
“…Earlier studies on pharmacogenomics mainly dealt with identification of genomic variants in γ‐globin, BCL11A, and HBS1L‐MYB, which might be responsible for the selective response to hydroxyurea treatment . Because so far there is no genomic biomarker on the basis of which hydroxyurea therapy can be adapted for SCD and β‐thalassemia patients, we decided to take a pharmacoproteomics approach. In the past decade rapid technical developments in tandem MS and label‐free quantification have resulted in meaningful understanding of pathological pathways, biomarkers, and drug mechanisms at the proteome level .…”
Section: Discussionmentioning
confidence: 99%
“…SCD is caused by an SNV in the β-globin gene which results in a Glu6Val substitution. This causes polymerization of hemoglobin S, resulting in erythrocytes with a sickle shape [6].…”
Section: Data For the African Contextmentioning
confidence: 99%
“…More genomics research is needed to better understand the link between genetics and different manifestations of SCD-associated diseases in different African populations [7]. There are also few studies on attempting to understand the link between genetics and variable responses to pain in SCD [6].…”
Section: Data For the African Contextmentioning
confidence: 99%
See 1 more Smart Citation